2017
DOI: 10.18865/ed.27.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Hypertension and Diabetes in Canada: Intersections between Racial Identity, Gender, and Income

Abstract: A growing body of research from the United States informed by intersectionality theory indicates that racial identity, gender, and income are often entwined with one another as determinants of health in unexpectedly complex ways. Research of this kind from Canada is scarce, however. Using data pooled from ten cycles (2001-2013) of the Canadian Community Health Survey, we regressed hypertension (HT) and diabetes (DM) on income in subsamples of Black women (n = 3,506), White women (n = 336,341), Black men (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
27
1
Order By: Relevance
“…That means sex and gender differential effects of a wide range of SEP indicators on many outcomes have been documented for children, adults, and older adults. Among adults, many studies have shown stronger health effects of income and other related SEP indicators for males than females [86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…That means sex and gender differential effects of a wide range of SEP indicators on many outcomes have been documented for children, adults, and older adults. Among adults, many studies have shown stronger health effects of income and other related SEP indicators for males than females [86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…The use of an intersectional framework represents a new way of understanding the complex nature of health inequities,22 and it may provide an improved awareness of the heterogeneous distribution of type 2 diabetes risk in the population 17. To the best of our knowledge, however, only one previous study from Canada has used an intersectional approach in the study of diabetes risk 23. Here, it should be emphasized that we are not referring to heterogeneity in terms of different diabetes phenotypes, but in terms of differences in the propensity for suffering from type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also suggests that prevalence rates in hypertension and diabetes are higher among south Asian and Black Canadians than White Canadians [15,16]. Another study highlights the complexity of the unequal distribution of hypertension and diabetes, which includes inordinately high risks of both outcomes for poor Black women and an absence of associations between income and both outcomes for Black men in Canada [17].…”
Section: Discussionmentioning
confidence: 91%